1990
DOI: 10.1007/bf00034860
|View full text |Cite
|
Sign up to set email alerts
|

State 1-State 2 transitions in the cyanobacterium Synechococcus 6301 are controlled by the redox state of electron carriers between Photosystems I and II

Abstract: The mechanism by which state 1-state 2 transitions in the cyanobacterium Synechococcus 6301 are controlled was investigated by examining the effects of a variety of chemical and illumination treatments which modify the redox state of the plastoquinone pool. The extent to which these treatments modify excitation energy distribution was determined by 77K fluorescence emission spectroscopy. It was found that treatment which lead to the oxidation of the plastoquinone pool induce a shift towards state 1 whereas tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
87
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(95 citation statements)
references
References 43 publications
7
87
1
Order By: Relevance
“…The redox state of photosynthetic electron transport chain functions as the key controller of the distribution of respiratory complexes (Liu et al, 2012), photosystem composition (Fujita et al, 1987), photosynthetic state transitions (Mullineaux and Allen, 1990), and the D, No significant changes in the cell length and width of Synechococcus is detected during inhibitor treatments for 24 h (P . 0.05, n = 500).…”
Section: Discussionmentioning
confidence: 99%
“…The redox state of photosynthetic electron transport chain functions as the key controller of the distribution of respiratory complexes (Liu et al, 2012), photosystem composition (Fujita et al, 1987), photosynthetic state transitions (Mullineaux and Allen, 1990), and the D, No significant changes in the cell length and width of Synechococcus is detected during inhibitor treatments for 24 h (P . 0.05, n = 500).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, during the phase transitions in HC-grown S. The state transition regulates the light-harvesting efficiency of photon energy by PSII and PSI. 30) State I is induced when PSI is photoexcited more than PSII. Fm′ in state I is higher than in state II.…”
Section: Relationships Between Phase Transition and State Transitionmentioning
confidence: 99%
“…PBS can transfer energy to both photosystem II (PSII) and photosystem I (PSI) [2], and energy distribution between PSII and PSI is regulated by a process called state transition [23,24]. Early reports showed that state transitions occurred in a time range of subseconds to seconds [25] and that this process is controlled by the redox state of electron carriers between PSI and PSII [26]. Liu et al [27] recently reported the isolation of a PBS-PSII-PSI mega-complex, and suggested that PBS does not need to change its spatial position during state transitions.…”
Section: Introductionmentioning
confidence: 99%